Geochemical and mineralogical characterization of critical elements in gold tailings from the La Cienega, Peru, and assessment of their reuse potential - Cotrina Teatino, Marco Antonio (2025)
Mine tailings represent a secondary resource of growing interest in the context of the energy transition and circular economy. This study evaluated the potential for recovering critical elements from Tailings Deposit I of the La Cienega site, Peru, through the integration of geochemical and mineralogical characterization tools and three-dimensional geostatistical modeling. A total of 68 samples were analyzed for cobalt (Co), nickel (Ni), lithium (Li), and phosphorus (P), and 10 samples for uranium (U) and tungsten (W). The results revealed a significant presence of these elements, with localized enrichment zones and distinct geochemical associations. Ni and Co exhibited spatial patterns consistent with their likely occurrence in residual sulfides, whereas Li, W, U, and P showed more heterogeneous distributions. Three-dimensional modeling performed using ordinary kriging and validated through Leave-One-Out (LOO) cross-validation, enabled the estimation of the distribution and potential resources of these critical elements within the deposit. Tonnage–grade curves indicate concrete opportunities for the design of selective recovery processes. This work contributes to the development of strategies for the comprehensive utilization of mine tailings as a secondary source of critical raw materials, reinforcing their role in more sustainable and circular mining.